2x+11=-9x-18

Simple and best practice solution for 2x+11=-9x-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+11=-9x-18 equation:


Simplifying
2x + 11 = -9x + -18

Reorder the terms:
11 + 2x = -9x + -18

Reorder the terms:
11 + 2x = -18 + -9x

Solving
11 + 2x = -18 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
11 + 2x + 9x = -18 + -9x + 9x

Combine like terms: 2x + 9x = 11x
11 + 11x = -18 + -9x + 9x

Combine like terms: -9x + 9x = 0
11 + 11x = -18 + 0
11 + 11x = -18

Add '-11' to each side of the equation.
11 + -11 + 11x = -18 + -11

Combine like terms: 11 + -11 = 0
0 + 11x = -18 + -11
11x = -18 + -11

Combine like terms: -18 + -11 = -29
11x = -29

Divide each side by '11'.
x = -2.636363636

Simplifying
x = -2.636363636

See similar equations:

| 9(z-6)=4(z-4) | | 9(x+5)=9(x+10) | | t=3+14t-5t^2 | | h(t)=3+14t-5t^2 | | -2x+2=-1 | | 5s+2=5c-2 | | -5n+3=-22 | | 2x+13=-3x-20 | | -1/5x=-12 | | 5t-4=-14 | | (x*2)-9=x | | 8x+12=-6x-18 | | -6(m-23)=1 | | a+b=cfindb | | 8+5v=-8(-8v+8)+v | | 1/7-11=1/4x-14 | | 3.2+2.2x=3x | | x(2x-3)(4x+1)=0 | | 2x^2-2=45 | | -x-4.7=9 | | x/4=4/3 | | c=37+22h | | 12x-y=-10 | | 1/2r=3 | | c=22h+37 | | -36-8n=-3(3n+2)-5n | | f(x)=-3x^2-30x-82 | | 0.2x/x=2.5 | | xsquared-8x=20 | | 40m+0.25=25m+0.45 | | 9(k-2/3)=33=0 | | sinx=0.36736578268 |

Equations solver categories